Single‐Phase All‐Solid‐State Lithium‐Ion Battery Using Li3V2(PO4)3 as the Cathode, Anode, and Electrolyte. Issue 26 (12th September 2017) - Inoishi, Atsushi; Omuta, Takuya; Yoshioka, Yuto; Kobayashi, Eiji; Kitajou, Ayuko; Okada, Shigeto
Abstract: To realize an ideal interface between electrode and electrolyte, a single‐phase all‐solid‐state lithium‐ion battery is studied using Li3 V2 (PO4 )3 ‐based NASICON‐type material as the cathode, anode, and electrolyte. A dense Li3‐x V2‐x Alx (PO4 )3 pellet with the Pt current collectors on both the front and back surfaces successfully demonstrates charge‐discharge reactions based on the V 3+ /V 2+ (anode) and V 3+ /V 4+ (cathode) redox systems at 373 K. Al substitutional doping for V brings the suppression of the electronic conductivity and increase in the ionic conductivity. As a result, Al‐doped material (Li3 V1.6 Al0.4 (PO4 )3 ) exhibites the best charge‐discharge performance in the Li3 V2‐x Alx (PO4 )3 system (x=0 ‐ 0.6) because of its high ionic conductivity and low electronic conductivity. The concept of a single‐phase battery with a single material offers a new approach to avoid side reactions during cell fabrication of oxide‐based all‐solid‐state lithium‐ion batteries. Abstract : A single‐phase all‐solid‐state lithium‐ion battery is studied using Li3 V2 (PO4 )3 ‐based NASICON‐type material as the cathode, anode, and electrolyte. A dense Li3‐x V2‐x Alx (PO4 )3 pellet with the Pt current collectors on both the front and back surfaces successfully demonstrates charge‐discharge reactions based on the V 3+ /V 2+ (anode) and V 3+ /V 4+ (cathode) redox systems at 373 K.